Potentiation of ceftazidime by avibactam against β-lactam-resistant Pseudomonas aeruginosa in an in vitro infection model. (10th January 2017) - Sy, Sherwin K. B.; Zhuang, Luning; Beaudoin, Marie-Eve; Kircher, Philipp; Tabosa, Maria A. M.; Cavalcanti, Noely C. T.; Grunwitz, Christian; Pieper, Sebastian; Schuck, Virna J.; Nichols, Wright W.; Derendorf, Hartmut
Abstract : Objectives: This study evaluated the in vitro pharmacodynamics of combinations of ceftazidime and the non-β-lactam β-lactamase inhibitor, avibactam, against ceftazidime-, piperacillin/tazobactam- and meropenem-multiresistant Pseudomonas aeruginosa by a quantitative time–kill method. Methods : MICs of ceftazidime plus 0–16 mg/L avibactam were determined against eight isolates of P. aeruginosa . Single-compartment, 24 h time–kill kinetics were investigated for three isolates at 0–16 mg/L avibactam with ceftazidime at 0.25–4-fold the MIC as measured at the respective avibactam concentration. Ceftazidime and avibactam concentrations were measured by LC-MS/MS during the time–kill kinetic studies to evaluate drug degradation. Results: Avibactam alone displayed no antimicrobial activity. MICs of ceftazidime decreased by 8–16-fold in the presence of avibactam at 4 mg/L. The changes in log10 cfu/mL at both the 10 h and 24 h timepoints (versus 0 h) revealed bacterial killing at ≥1-fold MIC. Significantly higher concentrations of ceftazidime alone, as compared with those of ceftazidime in combination, were required to produce any given kill. Without avibactam, ceftazidime degradation was significant (defined as degradation t 1/2  <  24 h), with as little as 19%  ±  18% of the original concentration remaining at 8 h for the most resistant strain. In combination with avibactam, ceftazidime degradation at ≥ 1-fold MIC was negligible. Conclusion: The addition of avibactam protected ceftazidime from degradation in a dose-dependent manner and restored its cidal and static activity at concentrations in combination well below the MIC of ceftazidime alone.